Repetitive Arm and Hand Movements (Complex Motor Stereotypy) in a Six-Year Boy - Koul, Roshan; Hora, Ravinder (Journal of Pediatric Epilepsy, 2020)
Abnormal movements are not uncommon in children. Most of these abnormal movements can be defined by the available criteria. Abnormal movements are easily diagnosed in adults. Most of these abnormal movements are well categorized and diagnosed by the defined characteristics. Sometimes it is difficult to diagnose an unusual movement disorder in children, particularly if it is rare and there are no investigations to prove the diagnosis. Repetitive arm and hand movements (complex motor stereotypy) is one such disorder which is rare and difficult to diagnose unless seen before. In this case report, we described a 6-year-old boy with this disorder, in whom it took 6 years to diagnose.
Keywords: movement disorder; repetitive movements; stereotypy; tics